2018
DOI: 10.1007/s00406-018-0916-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical activity on cognitive performance: a controlled clinical study in depressive patients

Abstract: Physical activity is a common adjunctive therapy in psychiatric and psychosomatic hospitals. In the present study, we assessed the effects of an exercise program, integrated into routine inpatient treatment, on cognitive performance and subjective severity of depression in a sample of patients suffering from major depression. We randomized n = 38 patients with unipolar depression to either physical exercise (n = 18) or occupational therapy as an active control treatment (n = 20). Both treatments were delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
10

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 23 publications
0
33
0
10
Order By: Relevance
“…In their study, 3 weeks of AE was associated with a significant reduction in symptom severity, which was not the case for the control condition (stretching activities). In contrast, Buschert et al (11) compared 3 to 4 weeks of AE to occupational therapy in a sample of 38 depressed inpatients and found no beneficial effect of AE on depressive symptoms. In summary, there is a current trend toward comparing AE to an active control group that usually consists of stretching activities rather than TAU or a waiting-list control group.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In their study, 3 weeks of AE was associated with a significant reduction in symptom severity, which was not the case for the control condition (stretching activities). In contrast, Buschert et al (11) compared 3 to 4 weeks of AE to occupational therapy in a sample of 38 depressed inpatients and found no beneficial effect of AE on depressive symptoms. In summary, there is a current trend toward comparing AE to an active control group that usually consists of stretching activities rather than TAU or a waiting-list control group.…”
Section: Introductionmentioning
confidence: 92%
“…Finally, there is a growing body of evidence supporting a beneficial effect of AE on cognitive symptoms associated with depression such as impairments of working memory and executive function (11, 2023). Since cognitive symptoms of depression often are a persisting problem not being properly targeted by antidepressants (24, 25), this may be another promising benefit of AE.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent reviews of physical, physiological, and biological therapies have been promising, analysis of these interventions is beyond the scope of this review . We refer the reader to studies on deep brain stimulation (Bergfeld et al, 2017;Kubu et al, 2017), repetitive transcranial magnetic stimulation (Noda et al, 2018), transcranial direct current stimulation, (Salehinejad et al, 2017;Martin et al, 2018), cognitive remediation (Bowie et al, 2013;Trapp et al, 2016;Motter et al, 2016), exercise (Brondino et al, 2017;Buschert et al, 2018) and other physical therapies (Greer et al, 2017;Listunova et al, 2018). Table 5 outlines the main study characteristics for novel therapies used for cognitive impairment in recent trials, generally as augmentation with concomitant antidepressant treatment, and only those with cognitive outcomes have been included.…”
Section: Evaluation Of Novel Treatments On Cognitive Impairmentmentioning
confidence: 99%
“…Positive but preliminary findings showed that augmentation with stimulants modafinil, LDX, and nicotine may improve attention, episodic and working memory, and executive function (Kaser et al, 2017;McIntyre et al, 2017b;Gandelman et al, 2018). While the benefits of exercise remain equivocal due to study designs, it is an effective and tolerable add-on therapy (Buschert et al, 2018). Skills training for MDD, similar to Computerised Interactive Remediation of Cognition -a Training for Schizophrenia (CIRCuiTS), could be constructive; if this was accessible, it could have similar positive effects to the 'online homework' used in CR trials (Reeder et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a randomized controlled study in patients with MDD, Buschert et al [5] showed improved reaction time and shortterm verbal memory after a 4-week-lasting aerobic exercise program. In this patient group and in patients with SZ [6], physical exercise is a feasible and easy-to-implement add-on therapy.…”
mentioning
confidence: 99%